Multicomponent Cyclizative 1,2‐Rearrangement Enabled Enantioselective Construction of 2,2‐Disubstituted Pyrrolinones - Li, Xing‐Zi; He, Yu‐Ping; Wu, Hua (Angewandte Chemie International Edition, 2024)
The 1,2‐rearrangement reaction is one of the most important approaches to construct carbon‐carbon bonds in organic synthesis. However, the development of catalytic asymmetric 1,2‐rearrangements is still far from mature and often suffers from problems such as complex substrates, single product structure, and lack of synthetic application. Multicomponent reaction has been recognized as a robust tool for the synthesis of diverse and tunable products from readily available starting material. Conceptionally and practically, the development of multicomponent asymmetric 1,2‐rearrangements is highly desirable. In this regard, we report herein a three‐component benzilic acid‐type rearrangement of 2,3‐diketoesters, aromatic amines and aldehydes for the asymmetric construction of synthetically challenging pyrrolinones bearing aza‐quaternary stereocenters. To the best of our knowledge, this reaction represents the first example of organocatalyzed multicomponent asymmetric 1,2‐rearrangements. The first organocatalyzed multicomponent asymmetric 1,2‐rearrangement is established, which provides a straightforward access to 2,2‐disubstituted pyrrolinones in excellent chemo‐ and stereoselectivities. This reaction also represents the first example of asymmetric catalytic construction of chiral pyrrolinones bearing aza‐quaternary stereocenters.